Literary hispanophobia and hispanophilia in Britain and the Low Countries (1550-1850) - Rodríguez Pérez, Yolanda, 1967- (Heritage and memory studies., 2020)
Spain has been a fruitful locus for the European imagination for centuries, and it has been most often perceived in black-and-white oppositions - either as a tyrannical and fanatical force in the early modern period or as an imaginary geography of a 'Romantic' Spain in later centuries. However, the image of Spain, its culture and its inhabitants did not evolve inexorably from negative to positive. From the early modern period onwards, it responded to an ambiguous matrix of conflicting Hispanophobic and Hispanophilic representations. Just as in the nineteenth century latent negative stereotypes continued to resurface, even in the Romantic heyday, in the early modern period appreciation for Spain was equally undeniable. When Spain was a political and military superpower, it also enjoyed cultural hegemony with a literary Golden Age producing internationally hailed masterpieces. This book explores the protracted interest in Spain and its culture, and it exposes the co-existent ambiguity between scorn and fascination that characterizes Western historical perceptions, in particular in Britain and the Low Countries, two geographical spaces with a shared sense of historical connectedness and an overlapping - and sometimes complicated - history with Spain.